Regulation of MAVS Expression and Signaling Function in the Antiviral Innate Immune Response - Ren, Zhihua; Ding, Ting; Zuo, Zhicai; Xu, Zhiwen; Deng, Junliang; Wei, Zhanyong (Frontiers in Immunology, 2020)
Viral infection is controlled by host innate immune cells that express specialized receptors for viral components. Engagement of these pattern recognition receptors triggers a series of signaling pathways that culminate in the production of antiviral mediators such as type I interferons. Mitochondrial antiviral-signaling protein (MAVS) acts as a central hub for signal transduction initiated by RIG-I-like receptors, which predominantly recognize viral RNA. MAVS expression and function are regulated by both post-transcriptional and post-translational mechanisms, of which ubiquitination and phosphorylation play the most important roles in modulating MAVS function. Increasing evidence indicates that viruses can escape the host antiviral response by interfering at multiple points in the MAVS signaling pathways, thereby maintaining viral survival and replication. This review summarizes recent studies on the mechanisms by which MAVS expression and signaling are normally regulated and on the various strategies employed by viruses to antagonize MAVS activity, which may provide new insights into the design of novel antiviral agents.